Moral Conflict: Balancing Human Rights and Worship Regulation in Indonesia - Lolong, Wenly Ronald Jefferson; Timomor, Adensi (Jurnal Moral Kemasyarakatan, 2025)
Religious freedom is a part of human rights that must be granted to every individual as a person living in a free country. The constitution guarantees the freedom to practice one’s religion as stated in Article 29, paragraph (2) of the 1945 Constitution of the Republic of Indonesia. Many practices violate religious freedom, and individuals face obstacles and violence in performing their worship. This research aims to examine the causes of violations of freedom of worship, factors contributing to intolerance, and the state's role in protecting victims of such violations. Using normative legal research methods, it focuses on identifying key issues and analyzing legal frameworks. The Indonesian Constitution guarantees religious freedom and the right to worship, as outlined in Article 28E and Article 29 of the 1945 Constitution. Despite this, intolerance in worship practices persists due to a lack of understanding and acceptance of diversity, which is seen as a divine creation rather than human choice. Contributing factors include economic inequality, legal injustices, political interests, differences in customs and doctrines, education gaps, and social disparities.